‘PUBLIC SPEAKING’ SEBAGAI BAGIAN DARI KOMUNIKASI EFEKTIF (KEGIATAN PKM di SMA KRISTOFORUS 2, JAKARTA BARAT) - Girsang, Lasmery Rosentauly Maissalinya (Jurnal Pengabdian dan Kewirausahaan, 2018)
ABSTRACT Everyone is able to speak, but only some who are able to gather words into beautiful language and can attract the public to hear it. So, simply speaking public speaking means the ability to speak by "playing" language in front of the public. Public speaking or public speaking is not something that is rare in today's advanced era. All individuals are required to be skilled in speaking in public to convey their goals. In the study of communication, the expertise of public speaking is part of effective communication that is conveying messages to the audience in a way that is appropriate and attracts attention. At present, public speaking is one of the absolute abilities needed in the global era. It is triggered by the demands of the times and the existing technology that forces individuals to compete to improve their quality. The importance of public speaking ability is inseparable from the definition of public speaking itself. In the 'Empowerment for the Community' (PKM) activities involving writers, public speaking training took place at SMA Kristoforus 2 West Jakarta. The reason for targeting students in these schools is none other than to equip students with knowledge related to public speaking skills. The majority of class XI students are not yet fully 'confident' when presenting themselves to the public. Therefore with the method of cermah and practice (practice), students are challenged to be brave in the future and present their opinions.Keywords: Effective communication, Public Speaking, Students